2017
DOI: 10.1038/srep43401
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printing of Meso-structurally Ordered Carbon Fiber/Polymer Composites with Unprecedented Orthotropic Physical Properties

Abstract: Here we report the first example of a class of additively manufactured carbon fiber reinforced composite (AMCFRC) materials which have been achieved through the use of a latent thermal cured aromatic thermoset resin system, through an adaptation of direct ink writing (DIW) 3D-printing technology. We have developed a means of printing high performance thermoset carbon fiber composites, which allow the fiber component of a resin and carbon fiber fluid to be aligned in three dimensions via controlled micro-extrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
132
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(140 citation statements)
references
References 71 publications
2
132
0
1
Order By: Relevance
“…For material extrusion processes, it is found that initially the fibers are not fully aligned in the composite filament, but shearing force between fibers and nozzle walls gives rise to alignment . Simulation studies carried out by Lewicki et al and Yang et al suggest that internal surface‐to‐volume ratio of the nozzle and rheology properties of the continuous phase fluid are two important factors to achieve efficient shear alignment in extrusion. Yang et al observed that the fiber alignment is affected by the flow split that occurs outside the nozzle, thus resulting in a complex velocity contour of resin flow.…”
Section: Future Outlookmentioning
confidence: 99%
“…For material extrusion processes, it is found that initially the fibers are not fully aligned in the composite filament, but shearing force between fibers and nozzle walls gives rise to alignment . Simulation studies carried out by Lewicki et al and Yang et al suggest that internal surface‐to‐volume ratio of the nozzle and rheology properties of the continuous phase fluid are two important factors to achieve efficient shear alignment in extrusion. Yang et al observed that the fiber alignment is affected by the flow split that occurs outside the nozzle, thus resulting in a complex velocity contour of resin flow.…”
Section: Future Outlookmentioning
confidence: 99%
“…The use of fibre reinforcements in 3D printing filaments for FFF is a topic of on-going research with both advancements in scientific literature as well as in commercial products, e.g. the MarkForged printers and the numerous reinforced thermoplastic filaments available on the market [2,24,31]. Table 1 shows an overview of the different studies performed to date on printing of reinforced filaments, showing the different methodologies and resulting relevant mechanical properties.…”
Section: Reinforced Filaments For Materials Extrusionmentioning
confidence: 99%
“…The technology of 3DP allows accurate fabrication of complicated sub-micron to few meters range structures from models by computer-aided design (CAD) or animation modeling software [1][2][3]. 3DP, which is widely regarded as a revolution in manufacturing technology, has been developed for a large range of applications, for example, in the field of aerospace and automotive [4], energy storage [5], electronics [6], engineered composites [7], biotechnology, tissue engineering [8], medical and pharmaceutical domains [9]. 3DP utilizes different techniques for the manufacturing of prototypes.…”
Section: Introductionmentioning
confidence: 99%